A Simplified Design of Clamping System and Fixtures for Friction Stir Welding of Aluminium Alloys - Hasan, Mohammed M.; M., Ishak; M. R. M., Rejab (Penerbit UMP, 2015)
Sound friction stir welds could be attained by using an active design of backing/clamping system with a proper selection of the welding parameters. This work presented a simplified design of fixtures and backing plates to be used for friction stir welding of aluminum alloys. The test-rig was constructed to prevent dispersal or lifting of the specimens throughout the joining process and to ensure uniform distribution of temperature along the plates. The workpieces were subjected to uniform lateral and vertical pressures by means of bolts and nuts. Compound backing plates and pressure bars with additional side plates were included to increase the heat sink. Several coupons of dissimilar aluminum alloys AA7075 and AA6061 were joined to inspect the validity of this design. The tests showed promising results with defects - free welds, good strength and smooth surface finish without geometric imperfection and gap creation between the welded specimens . Efficiency of the joint reached its maximum value of about 82% with respect to the ultimate strength of the AA6061 alloy at 1100 rpm rotation speed and 300 mm/min feed. These results encourage using and improving th e present design for future studies of friction stir welding